444 Sexting, Fraping and Hyper-Tweeting - what should Paediatricians be doing to Help?. (October 2012) - Onugha, NN; Finlay, F
Abstract : Unwanted sexual solicitation, online harassment, cyber-bullying and depression are all associated risks of social media to adolescents. More than a fifth of teenagers log on to a social media site at least ten times a day, 75% own mobile phones and of these, 25% use them for social media, 54% for texting and 24% for instant messaging. Adolescents often lack awareness of 'the digital footprint'; posting inappropriate messages, private and/or explicit pictures and videos and failing to recognise that 'what goes online, stays online'. Clinicians often see the consequences of these actions, for example, sexual abuse following meeting "friends" online, self harm following cyber-bullying and near-miss suicides following activities like "the choking game" viewed online. Yet not all social media is bad. Professionals are in a key position to sign-post useful information and health advice via social media; promoting a healthy lifestyle, a balanced diet and sexual health screening. The American Academy of Pediatrics (AAP) has published policy statements highlighting the impact of mass media and calling for media education to be a key goal for paediatricians. Professionals can provide anticipatory guidance to families, promoting wise-media choices as well as discussing the potential hazards. The AAP have developed a 'Media History form' to facilitate discussion. We believe that professionals need to work together to ensure that adolescents can enjoy the benefits offered by social media while minimising the risks - how can we best achieve this?